2015 IEEE First International Conference on Big Data Computing Service and Applications 2015
DOI: 10.1109/bigdataservice.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Security on Consumer E-Loyalty: A Study of Online Tourism Purchasing

Abstract: With the development of e-commerce and smart tourism, the combination of tourism and the internet has caused tourism purchasing in China to shift from traditional channels to online ones. However, while online tourism consumption has many advantages there are also high associated security risks. Understanding how perceived security impacts online tourism purchasing behavior is extremely important for tourism ecommerce enterprises. In this paper, we adopt the self-regulatory process proposed by Bagozzi (1992) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…The decrease in future consuming intentions and increase in defensive behaviors confirmed the seriousness of the negative effect of data leaking scandals on tourism platforms. This finding is in line with findings from previous studies that when customers feel concerned about security in online purchasing, their purchasing loyalty tends to decline ( Cui et al, 2015 ). Considering that presenting a vignette can already produce such large effects, this study highlights the importance of data security to keep customers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The decrease in future consuming intentions and increase in defensive behaviors confirmed the seriousness of the negative effect of data leaking scandals on tourism platforms. This finding is in line with findings from previous studies that when customers feel concerned about security in online purchasing, their purchasing loyalty tends to decline ( Cui et al, 2015 ). Considering that presenting a vignette can already produce such large effects, this study highlights the importance of data security to keep customers.…”
Section: Discussionsupporting
confidence: 93%
“…The issue of online platforms leaking customers’ private data (e.g., credit card information) has attracted increasing attention, as it may cause serious consequences such as reduction in customers’ consumption intentions to continue visiting these platforms (see Baruh et al, 2017 for a meta-analytical review). Among which, leaking of personal data hold by online tourism platforms may be particularly concerning, since these data cover customers’ sensitive financial and personal information such as flight and hotel reservation and price ( Cui et al, 2015 ). As a matter of fact, the scandal that one of the biggest tourism platforms in China leaked customers’ personal data has caused public panic about data security ( Cui et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without confidence in security, exchanges between hotel website and tourist might be restricted. In an attempt to invocate trust on the tourists, assurances of secure financial transactions and data privacy can be manifested (Cui et al, 2015). Therefore, it is suggested that perceived security is a significant antecedent of e-trust engendered because of the internet nature.…”
Section: Perceived Securitymentioning
confidence: 99%
“…The second most widely examined consequence of consumer innovativeness is consumers' attitudinal and behavioral responses to brands. Brand responses cover response to brand extension, satisfaction, brand loyalty, brand engagement, repurchase intention and brand switching (Chang et al, 2019;Cui et al, 2018;Eren-Erdogmus et al, 2018;Kelley and Alden, 2016;Quoquab et al, 2018;San-Martin and Lopez-Catalan, 2013;Simmons et al, 2017). Another consequence of consumer innovativeness examined in the literature is consumers' product evaluations.…”
Section: Figure 5 Consequences Of Consumer Innovativenessmentioning
confidence: 99%